They've just multiplied everything by -1 to make it a bit cleaner.
I am a little confused with this one and I have a test tomorrow
Why does y = -3x -3 (slope-intercept form) become 3x + y + 3 = 0 in standard form instead of -3x-y-3 = 0?
and - 3 = y-(-10)/x-1 should be - 3x-y-7 = 0 so why is it 3x+y+7 = 0?
Mind explaining? Thanks so much!
Subtracting y from both sides
It is good to note here that if we would have added (3x+3) to both sides, the problem would have been more aesthetically pleasing while maintaining equivalency:
This form is not only equivalent to the other, but more conventional, and therefore what your teacher is going to be looking for first. Both answers are correct.
By the way, I like your avatar.